Reflections on Language, Culture and Equity in Teaching Mathematics at a Bilingual Primary School in the United States - Musanti, Sandra I.; Celedon-Pattichis, Sylvia; Marshall, Mary E. (GIST – Education and Learning Research Journal, 2012)
This study investigates K-1 teachers´ perceptions, practices, and equity issues in the integration of contextualized problem solving into the curriculum as a way to adapt instruction to meet the needs of Latino students who were English language learners. We draw from three bodies of literature: Cognitively Guided Instruction, language and culture as pedagogical resources, and equity issues in mathematics. This qualitative study takes place in the context of a situated professional development between bilingual teachers and researchers in a southwestern elementary school in the United States. Data sources included classroom observations, videotaped lessons, and interviews with the teachers. Through classroom episodes, this study illustrates how both teachers: (1) valued the integration of contextualized problem solving into their curriculum and used language and culture to scaffold understanding of complex mathematics concepts, (2) prioritized the use of the native language in their teaching and the development of different ways to communicate mathematically their ideas and strategies, and (3) prioritized equitable teaching by valuing and promoting a student centered approach to teaching as well as students´ identity as mathematics learners.